Macroprudential regulation, credit spreads and the role of monetary policy - Tayler, William J.; Zilberman, Roy (Journal of Financial Stability, 2016)
We study the macroprudential roles of bank capital regulation and monetary policy in a borrowing cost channel model with endogenous financial frictions, driven by credit risk, bank losses and bank capital costs. These frictions induce financial accelerator mechanisms and motivate the examination of a macroprudential toolkit. Following credit shocks, countercyclical regulation is more effective than monetary policy in promoting price, financial and macroeconomic stability. For supply shocks, combining macroprudential regulation with a stronger anti-inflationary policy stance is optimal. The findings emphasize the importance of the Basel III accords in alleviating the output-inflation trade-off faced by central banks, and cast doubt on the desirability of conventional (and unconventional) Taylor rules during periods of financial distress.